LC-MS-based metabolomics reveals the mechanism of anti-gouty arthritis effect of Wuwei Shexiang pill - Lang, Jirui; Li, Li; Quan, Yunyun; Tan, Ruirong; Zhao, Jinbiao; Li, Min; Zeng, Jin; Chen, Shilong; Wang, Ting; Li, Yong; Zhao, Junning; Yin, Zhujun (Frontiers in Pharmacology, 2023)
Wuwei Shexiang Pill (WSP) is a Tibetan traditional medicine, which has been demonstrated to exhibit potent anti-inflammatory and anti-gout effects. However, the specific pharmacological mechanism is not elucidated clearly. In the present study, liquid chromatography-mass spectrometry (LC-MS)-based metabolomics was applied to investigate the alteration of serum metabolites induced by WSP treatment in MSU-induced gouty rats. Subsequently, bioinformatics was utilized to analyze the potential metabolic pathway of the anti-gout effect of WSP. The pharmacodynamic data discovered that WSP could ameliorate ankle swelling and inflammatory cell infiltration, as well as downregulate the protein expression of IL-1β, p-NF-κB p65, and NLRP3 in the synovial membrane and surrounding tissues of gouty ankles. LC-MS-based metabolomics revealed that there were 30 differential metabolites in the serum between sham-operated rats and gouty ones, which were mainly involved in the metabolism of fructose and mannose, primary bile acid biosynthesis, and cholesterol metabolism. However, compared to the model group, WSP treatment upregulated 11 metabolic biomarkers and downregulated 31 biomarkers in the serum. KEGG enrichment analysis found that 27 metabolic pathways contributed to the therapeutic action of WSP, including linoleic acid metabolism, phenylalanine metabolism, and pantothenate and CoA biosynthesis. The comprehensive analysis-combined network pharmacology and metabolomics further revealed that the regulatory network of WSP against gout might be attributed to 11 metabolites, 7 metabolic pathways, 39 targets, and 49 active ingredients of WSP. In conclusion, WSP could ameliorate the inflammation of the ankle in MSU-induced gouty rats, and its anti-gout mechanism might be relevant to the modulation of multiple metabolic pathways, such as linoleic acid metabolism, phenylalanine metabolism, and pantothenate and CoA biosynthesis. This study provided data support for the secondary development of Chinese traditional patent medicine.